2019
DOI: 10.1016/j.ejca.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab plus ipilimumab versus chemotherapy as first-line treatment in advanced non–small-cell lung cancer with high tumour mutational burden: patient-reported outcomes results from the randomised, open-label, phase III CheckMate 227 trial

Abstract: B a c k g r o u n d : I n t h e p h a s e I I I C h e c k M a t e 2 2 7 s t u d y , fi r s t-l i n e nivolumab þ ipilimumab significantly prolonged progression-free survival (co-primary endpoint) versus chemotherapy in patients with advanced nonesmall-cell lung cancer (NSCLC) and high tumour mutational burden (TMB; !10 mutations/megabase). Aim: To evaluate patient-reported outcomes (PROs) in this population. Methods: Disease-related symptoms and general health status were assessed using the validated PRO quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 30 publications
6
146
0
3
Order By: Relevance
“…The differences of HR QoL evaluated with different PROs for patients treated with the two treatments under evaluation and their concordance about the outcome evaluated in the study were reported. 39 Disease progression had a significant adverse impact on many PROs' endpoints; 40 PROs showed that they were useful in identifying patients with advanced NSCLC who are likely to have significantly lower survival. 41 The prognostic power of overall QoL on the survival of lung cancer patients and the advantages for lung cancer survivors reporting to be physically active was demonstrated versus those who were not physically active; 42 the early detection of symptomatic relapse and management of symptoms through a webmediated individualized follow-up strategy provided an improvement in quality of life and overall survival.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences of HR QoL evaluated with different PROs for patients treated with the two treatments under evaluation and their concordance about the outcome evaluated in the study were reported. 39 Disease progression had a significant adverse impact on many PROs' endpoints; 40 PROs showed that they were useful in identifying patients with advanced NSCLC who are likely to have significantly lower survival. 41 The prognostic power of overall QoL on the survival of lung cancer patients and the advantages for lung cancer survivors reporting to be physically active was demonstrated versus those who were not physically active; 42 the early detection of symptomatic relapse and management of symptoms through a webmediated individualized follow-up strategy provided an improvement in quality of life and overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…Data on PRO completion rates are available for 20 studies (60.61%) (Table 3), only in 3 studies (15%) was it lower than 80%; 44,47,59 for the others 17 (85%) it was higher than 80%. 35,36,39,40,45,48,49,51,52,[55][56][57][58]61,[66][67][68] Only in one study (5%) did the authors report a completion rate of 100%. 52 In most cases, frequencies decreased over time from baseline to subsequent measurements.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…NIVO + IPI showed significant advantages over sunitinib in advanced renal cell carcinoma (Motzer et al, 2018), which led to FDA approval of NIVO + IPI for the treatment of advanced renal cell carcinoma (Schuyler, 2018;Cella et al, 2019). Another study (Reck et al, 2019) showed that first-line NIVO + IPI led to continuous early improvement in patients with advanced NSCLC and high TMB compared with chemotherapy. Japan's single-arm experiment (Namikawa et al, 2018) also highlighted the advantages of NIVO + IPI.…”
Section: Discussionmentioning
confidence: 99%
“…A potential limitation of the present study is represented by its design, in which anti-PD-1 therapy was given in the clinical care setting rather than a randomized controlled trial. Therefore, no comparison has been made to other biomarkers, such as tumor mutational burden [23], as these biomarkers are not yet clinically validated for the selection of treatment [24]. One could argue that this real-world design brings the evaluation of biomarkers closest to daily practice.…”
Section: Discussionmentioning
confidence: 99%